448-P: Serum Inflammatory Markers Are Not Correlated with Detection of Osteomyelitis by 99mTC-WBC SPECT/CT Imaging in Subjects with Diabetes and Foot Infection - SHERWOOD, AMBER; RUBITSCHUNG, KATIE L.; KILLEEN, AMANDA L.; CRISOLOGO, PETER; GRIGOROPOULOS, KATERINA; PAJOUH, AMANDA; KEP, JENNIFER; WUKICH, DANE; FONTAINE, JAVIER LA; LAVERY, LAWRENCE A.; OZ, ORHAN K. (Diabetes (New York, N.Y.), 2021)
Osteomyelitis is a common complication in diabetic foot ulcers. Accurate and early detection of diabetic foot osteomyelitis (DFO) is key to optimizing clinical outcomes and avoiding amputation. Using bone biopsy histopathology as the gold diagnostic standard, we evaluate the sensitivity and specificity of radiolabeled white blood cell imaging combined with CT (99mTc-WBC SPECT/CT) for the evaluation of DFO. We also assess the ability of the inflammatory markers CRP and ESR to predict osteomyelitis diagnosis by 99mTc-WBC SPECT/CT imaging. Subjects with diabetes and foot ulcerations presenting to a large tertiary care facility were examined by podiatry. Of the 48 subjects who consented to participation, 44 completed imaging, labwork, and underwent biopsy. Serum CRP and ESR were collected within three days of consent. In all cases, WBC imaging studies were performed prior to biopsy. The WBC SPECT/CT scans were read by an experienced Nuclear Medicine radiologist. Pathology was performed in the hospital laboratory and interpreted by a pathologist experienced in MSK infections. SPECT/CT and pathology reads were coded as either positive or negative for osteomyelitis. Sensitivity and specificity of 99mTc-WBC SPECT/CT for DFO diagnosis was 90.9% and 73.7%, respectively. WBC imaging had a PPV of 80.0%, and 87.5% NPV (n=41). CRP and ESR serum levels were grouped according to positive or negative DFO diagnosis as determined by WBC scan. Neither CRP (p=0.9895) nor ESR levels (p=0.8382) were correlated with DFO diagnosis based on WBC imaging results. Using bone biopsy results as the reference standard, radiolabeled 99mTc-WBC SPECT/CT demonstrates sensitivity for DFO. However, CRP and ESR were not found to be predictive in the diagnostic interpretation of 99mTc-WBC SPECT/CT imaging for the diagnosis of DFO.